(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The BPSO and police law enforcers have implemented guidelines to ensure the safety and security of individuals in the community. Peace and order is one of the major concerns addressed in each agency. In the overall evaluation of the respondents in terms of patrol schedules, CCTV cameras, and gates per area, Lucia, Quezon City, rated good. The majority of the respondents said that teaching the locals how to keep the barangay peaceful and orderly was the most important step. The residents would be able to take an active role in initiatives to preserve peace and order in the barangay. Hence, the researchers advise that teaching them is important. Additionally, it will be able to give the locals the tools they need to become good citizens. It is also advised that a meeting of the barangay staff and citizens be held to explore ways to enhance the execution of peace and order in the barrio. Doing this will also solve the issues that the locals have with the CCTV cameras that have been placed, the need for more cameras, and the locals’ worry about the neighborhood gates.